Are children driving the gender wage gap?: Comparative evidence from Poland and Hungary1. Issue 2 (1st February 2016) - Cukrowska‐Torzewska, Ewa; Lovasz, Anna
Abstract: We examine how much children and the responsibilities related to them contribute to the divergence of men's and women's wages, and consequently, to the formation of the gender wage gap. To derive the relative contribution of gender‐specific parent gaps to the overall gender wage gap, we provide a modification of the Oaxaca–Blinder decomposition and include simultaneous corrections for selection into employment and parenthood. The results show that the fatherhood wage premium contributes most significantly to the gender wage gap, especially in Poland. The motherhood penalty is also significant, while the role of the gender gap among childless individuals is small.